Nickel core–palladium shell nanoparticles grown on nitrogen-doped graphene with enhanced electrocatalytic performance for ethanol oxidation. Issue 40 (5th April 2016) - Zhang, Mingmei; Li, Yuan; Pan, Denghui; Yan, Zaoxue; Meng, Suci; Xie, Jimin
Abstract : Herein, we report a facile two-step strategy for green synthesis of nickel core–palladium shell nanoclusters on nitrogen-doped graphene (Ni@Pd/NG) without any surfactant and additional reducing agent. Abstract : Herein, we report a facile two-step strategy for green synthesis of nickel core–palladium shell nanoclusters on nitrogen-doped graphene (Ni@Pd/NG) without any surfactant and additional reducing agent. During the synthesis, nitrogen-doped graphene acted as both the active substance and support by taking advantage of its moderate reducing and highly dispersing capacities. Characterization indicated that a uniform dispersion of Ni@Pd nanoparticles on nitrogen-doped reduced graphene oxide had a 2.8 nm average particle size. Unexpectedly, the as-prepared Ni@Pd/NG hybrid exhibited much greater activity and stability than that of Pd/graphene and commercial Pd/C electrocatalyst at the same Pd loadings. Possible mechanisms for the enhanced electrocatalytic performance of nitrogen-doped reduced graphene oxide after combining with Ni@Pd are proposed. The present study provides an efficient strategy to synthesize highly efficient electrocatalysts.